METHODS FOR EVALUATION AND TRAINING OF MANAGEMENT PERSONNEL - Rakhimova Dilfuza Nigmatovna; Khurramov Sanjar Ravshanovich (Scholar Express Journals, 2023)
Today, there are several types of selection of a candidate for leadership and determination of his / her qualifications, one of which is the method of recommending a candidate for this or that position by senior managers. A manager who selects staff for a lower-level management position first approaches the characteristics of the person being selected based on his or her goals. In the main cases it appears in a broken form in the character of the person and is also felt in the course of his practical work. The goals and interests of a selective leader can take two forms: private goals, interests of the organization or employees
Keywords: organization; selective; employees